Individual Investments in Education and Health: Policy Responses and Interactions - Jared C. Carbone; Snorre Kverndokk (Center for Economic Studies and ifo Institute (CESifo), 2016)
Empirical studies show that years of schooling are positively correlated with good health. The implication may go from education to health, from health to education, or from factors that influence both variables. We formalize a model that determines an individual's demand for knowledge and health based on the causal effects, and study the impacts on the individual's decisions of policy instruments such as subsidies on medical care, subsidizing schooling, income tax reduction, lump sum transfers and improving health at young age. Our results indicate that income redistribution policies may be the best instrument to improve welfare, while a medical care subsidy is the best instrument for longevity. Subsidies to medical care or education would require large imperfections in these markets to be more welfare improving than distributional policies.
Keywords: C61; D91; I12; I21; 330; demand for health; demand for education; human capital; numerical modeling; causality